2014
DOI: 10.1111/cas.12496
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐1 study of abiraterone acetate in chemotherapy‐naïve Japanese patients with castration‐resistant prostate cancer

Abstract: Persistent androgen synthesis under castration status in adrenal gland, testes and tumor cells is thought to be one of the major causes of development and progression of castration-resistant prostate cancer (CRPC). Abiraterone acetate (AA), the prodrug of abiraterone, which is an inhibitor of androgen synthesis enzymes, was evaluated for pharmacokinetics, pharmacodynamics, preliminary efficacy and safety in Japanese patients with CRPC in a phase-1, open-label and dose-escalation study. Chemotherapy-naïve Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This difference in the incidence rates of hypertension could partly be explained by the lower daily dose of prednisone used in LATITUDE (5 mg/day) ( 5 ) compared with the other studies that used 10 mg/day ( 4 , 9 , 11 , 13 ). The incidence of hepatotoxicity in this subgroup analysis was comparable with that of the IA of Japanese subgroup ( 17 ) and previous studies conducted in Japanese patients with mCRPC ( 10–13 ). Incidence of grade 3 or 4 AEs of cardiac disorders in this Japanese subgroup analysis was similar to that of the IA of Japanese subgroup ( 17 ), and a previous study was conducted in patients with chemotherapy-naïve mCRPC ( 21 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This difference in the incidence rates of hypertension could partly be explained by the lower daily dose of prednisone used in LATITUDE (5 mg/day) ( 5 ) compared with the other studies that used 10 mg/day ( 4 , 9 , 11 , 13 ). The incidence of hepatotoxicity in this subgroup analysis was comparable with that of the IA of Japanese subgroup ( 17 ) and previous studies conducted in Japanese patients with mCRPC ( 10–13 ). Incidence of grade 3 or 4 AEs of cardiac disorders in this Japanese subgroup analysis was similar to that of the IA of Japanese subgroup ( 17 ), and a previous study was conducted in patients with chemotherapy-naïve mCRPC ( 21 ).…”
Section: Discussionsupporting
confidence: 87%
“…Abiraterone acetate (AA) is a selective inhibitor of CYP17α hydroxylase enzyme that irreversibly inhibits intra- and extra-tumoral androgen biosynthesis. Addition of abiraterone acetate plus prednisone (AAP) to ADT has demonstrated a significant improvement in overall survival (OS) in patients with mCRPC in both chemotherapy-naïve and post-chemotherapy setting, in the global ( 4 , 9 ) and Japanese populations ( 10–13 ). The addition of AAP to ADT was associated with lowering of prostate tissue androgens in men with localized prostate cancer (PC), which suggests its role in inhibiting the extra-gonadal androgen biosynthesis and preventing progression to castration resistance in mHNPC patients ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The patient eligibility criteria for the clinical trials of AA have already been reported (13,14). The summary of eligibility is as follows: patients had mCRPC and had not received cytotoxic chemotherapy.…”
Section: Patientsmentioning
confidence: 99%
“…Interestingly, similar results were seen in abiraterone acetate‐treated cells as seen in SR‐treated cells (Supplementary Figure S3A‐D). This effect occurred at the pharmacologically relevant and non‐toxic concentration of 1 µM, similar to blood concentrations of patients after taking this medication; tissue concentrations would be expected to be higher . Cotreatment with SR media and abiraterone promoted formation of more projections than treatment with SR media alone ( P < 0.0005, one way ANOVA with Sidak's multiple comparisons).…”
Section: Resultsmentioning
confidence: 65%